Treacle is Upregulated in Cancer and Correlates With Poor Prognosis - Oxe, Kezia Catharina; Larsen, Dorthe Helena (Frontiers in Cell and Developmental Biology, 2022)
Treacle/TCOF1 is an adaptor protein specifically associated with nucleolar chromatin. In the nucleolus it stimulates ribosome biogenesis, thereby promoting growth and proliferation. A second role of Treacle has emerged as a coordinator of the nucleolar responses to DNA damage, where it facilitates nucleolar DNA repair and cellular survival after genotoxic insults. The involvement of Treacle in multiple fundamental processes such as growth, proliferation, and genome stability, which are tightly linked to cancer, raises the question of Treacle’s role in the development of this disease. On one hand, overexpression of Treacle could stimulate nucleolar transcription and ribosome biogenesis providing a growth advantage in cancer cells. On the other hand, the function of Treacle as a gatekeeper in response to nucleolar DNA damage could favor mutations that would impair its function. In this perspective, we analyze paired Treacle expression data from the Cancer Genome Atlas (TCGA) and correlate expression with patient survival in different cancer types. We also discuss other recently published observations of relevance to the role of Treacle in cancer. In light of these new observations, we propose possible roles of Treacle in carcinogenesis and discuss its potential as a therapeutic target.